Analysis of International Experiences in Constructing the Information System of Education Management in the Field of Technical and Vocational Education and Training - Lesnikova, M. V. (Statistics of Ukraine, 2019)
Education Management Information System (EMIS) is an organized group of information and documentation services that collects, stores, processes, analyzes and disseminates information on the planning and management of the education system. Each country tend to have own EMIS because of the differences in local systems of education and training. EMIS in the field of Technical and Vocational Education and Training (TVET), or TVET-MIS, is a consolidated EMIS for timely access to high quality information. The analysis showed that in all the countries under study the owner of EMIS in the field of vocational education is the Ministry of Education. Data is collected in the vast majority of countries, with exception of Brazil and Pakistan, from public vocational education institutions, and cover the formal education sector. Indicators contained in EMIS for professional (vocational) education provide the possibility of international comparisons, methodological soundness and simplicity of making statistical reports; they provide the user with the opportunity to generate the necessary information independently (an example is Open EMIS Core – TVET-MIS), form the extended database of registers with wide possibilities for searching the necessary information, tracing the trajectory of employment of graduates of professional (vocational) education institutions. These systems are characterized by: the availability of indicators of the effectiveness of the system of professional (vocational) education (examples are MLDS, Maryland and TVET-MIS – Career Tech, Ohio, USA), the coverage of professional (vocational) education institutions in public and private sectors, the successful coordination of the system of professional (vocational) education with the stakeholders (an example is NEMIS system in Pakistan), a comprehensive electronic system for collecting, managing and analyzing data from the system of professional (vocational ) education, despite economic instability in a country (an example is TAALIM system, Afghanistan), coverage of the informal professional (vocational) education sector, self-contained computerized data collection system that uses a centralized procedure for extracting primary data on one date for all institutions (an example is SISTEC system, Brazil).